(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Yazid M, Bastianudin A, Octavia B, Putra TD, Rachmani LD, Putri KNA. 2023. Indigenous filamentous fungi isolated from zirconia processing wastewater as a potential biosorbent for aqueous thorium(IV) ions. Biodiversitas 24: 6825-6835. This research focused on exploring indigenous thorium-tolerant fungal isolated from zirconia processing wastewater as a biosorbent for thorium. The objective of present study was to isolate, purify, identify, and analyze the selected capabilities of indigenous fungal biomass in adsorbing thorium from aqueous solution, with the aim of obtaining valuable technical data for its application as a bioremediation agent for technologically enhanced naturally occurring radioactive material (TENORM) wastewater containing thorium. The results showed that total five indigenous fungal isolates, namely two isolates of Penicillium sp. (T2, T4), Rhizoctonia sp. (T3), Mycelia sterilia (T5), and Aspergillus sp. (T6) were isolated from the samples. The result of tolerance index values revealed that two isolates i.e., Penicillium sp. (T2), Penicillium sp. (T4) and a Mycelia sterilia (T5) exhibited high tolerance, while Rhizoctonia sp. (T3) and Aspergillus sp. (T6) showed very high tolerance to thorium. Consequently, Rhizoctonia sp. (T3) was selected for the biosorption study based on the highest tolerance index value obtained. The optimal pH for biosorption was found to be 4 with 30 minutes of contact time and an 80°C temperature. The optimal biosorption efficiency with initial concentrations of 50 and 100 ppm was 97.53 and 90.88%, respectively. In conclusion, based on the obtained technical data, the Rhizoctonia sp. (T3) biomass shows significant potential as a bioremediation agent for wastewater containing thorium.